Advancements in 5G Technology: Enhancing Connectivity and Performance in Communication Engineering - Patel, Bhavik; Yarlagadda, Vamsi Krishna; Dhameliya, Niravkumar; Mullangi, Kishore; Vennapusa, Sai Charan Reddy (Engineering International, 2022)
The present research delves into how 5G technology developments can improve communication engineering performance and connectivity. The primary goals are to assess 5G’s technical viability, performance potential, and real-world obstacles while offering recommendations for best practices in implementation and use. The study synthesizes current literature, research papers, and industry reports using a secondary data-based review technique to examine the technological underpinnings, performance improvements, real-world applications, and future directions of 5G. According to key findings, 5G dramatically improves data rates, lowers latency, and allows for ample device connectivity, opening up new possibilities for revolutionary applications in industries like industrial automation, smart cities, and healthcare. Strategic policy interventions are necessary to address cybersecurity risks, coverage restrictions, interoperability issues, and expensive infrastructure costs. To overcome these issues, provide fair access, and optimize the socioeconomic benefits of 5G, policymakers are encouraged to prioritize spectrum allocation, simplify regulatory frameworks, and provide incentives for investments. Future studies and developments in Edge Computing and AI-driven network optimization are emphasized as essential to improving 5G networks even more. The potential of 5G to alter communication engineering and accelerate inclusive digital transformation is shown by this thorough examination.